1997
DOI: 10.1021/bp970103u
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stress Thickening of Dextran/Concanavalin A Solutions Used as Sensitive Fluids in a Viscosimetric Affinity Assay for Glucose

Abstract: Glucose-dependent low-stress and high-stress rheology of a sensitive fluid (SF) containing high-molecular-weight dextran (30 g/L) and Concanavalin A (ConA, 10 g/L) was studied to define conditions for reproducible glucose determination by a viscosimetric sensor. The viscosity of the investigated SF was reproducibly glucose-dependent only at sufficient shear stresses (>0.5 Pa). Rheometric parameters measured at low stresses (<0.1 Pa) were strongly dependent on the shear history. Low-stress viscosity measured af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In particular, methods that use equilibrium affinity binding of glucose have shown great promise [5]–[8]. These methods, in which glucose is not consumed, do not carry the risk of interfering with the local glucose concentration in the tissue or generating erosive reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, methods that use equilibrium affinity binding of glucose have shown great promise [5]–[8]. These methods, in which glucose is not consumed, do not carry the risk of interfering with the local glucose concentration in the tissue or generating erosive reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the affinity bonds to the viscosity of the SL is resistant to a shear stress larger than 1500 Pa (Figure 5), which could not be tested with the precision rheometer used in our earlier study (8). The high glucose sensitivity of F r at strongly increased shear stress demonstrates that the tendency stated previously (8) is continued in the range of high shear forces. The dextran/ConA solution shows less shear‐thinning in the absence of the sugar than in its presence, since the sugar destabilizes the cross‐links between dextran molecules of neighboring shear planes.…”
Section: Discussionmentioning
confidence: 93%
“…As a result of the strong modulation of the viscosity by ConA and glucose, a simple test based on the use of glass capillaries was sufficient to demonstrate the potency of the viscometric affinity assay and to describe the principle course of the characteristic curves of the lectin and the sugar (7). A rheologic study (8) showed that the sugar effect on the shear viscosity of the SL is reproducible at sufficient shear stress (1−100 Pa), whereas viscosity measured at very low shear stress (<0.2 Pa) is strongly dependent on prior shear treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of free glucose displaces the polysaccharide reversibly from the con A receptor sites, dismantling the connections, and producing a sol. The rheology of the material is dependent on the glucose content and has been described previously (Beyer, Ehwald, & Fleischer, 1997). Variations are documented in which the polysaccharide has been replaced by semisynthetics such as polysucrose and glucosesubstituted acrylics (Valuev, Chupov, Stayton, & Plate, 1997).…”
Section: Introductionmentioning
confidence: 94%